Smart Textile‐Integrated Microelectronic Systems for Wearable Applications. Issue 5 (5th July 2019) - Shi, Jidong; Liu, Su; Zhang, Lisha; Yang, Bao; Shu, Lin; Yang, Ying; Ren, Ming; Wang, Yang; Chen, Jiewei; Chen, Wei; Chai, Yang; Tao, Xiaoming
Abstract: The programmable nature of smart textiles makes them an indispensable part of an emerging new technology field. Smart textile‐integrated microelectronic systems (STIMES), which combine microelectronics and technology such as artificial intelligence and augmented or virtual reality, have been intensively explored. A vast range of research activities have been reported. Many promising applications in healthcare, the internet of things (IoT), smart city management, robotics, etc., have been demonstrated around the world. A timely overview and comprehensive review of progress of this field in the last five years are provided. Several main aspects are covered: functional materials, major fabrication processes of smart textile components, functional devices, system architectures and heterogeneous integration, wearable applications in human and nonhuman‐related areas, and the safety and security of STIMES. The major types of textile‐integrated nonconventional functional devices are discussed in detail: sensors, actuators, displays, antennas, energy harvesters and their hybrids, batteries and supercapacitors, circuit boards, and memory devices. Abstract : Smart textile‐integrated microelectronic systems (STIMES) have been extensively explored for their potential in health monitoring, the Internet‐of‐Things (IoT), smart cities, and robotics. Recent examples of functional materials, major fabrication processes, functional devices, system architectures and heterogeneous integration, and applications of smart textile components are presented. The safety and security of STIMES are also discussed.